Handmade for the garden : 75 ingenious ways to enhance your outdoor space with DIY tools, pots, supports, embellishments, and more - Guagliumi, Susan, 1948- (STC Craft, 2014)
Presents seventy-five projects for making garden structures and accessories using inexpensive, readily-available materials, including such items as rustic fencing, plant markers, painted terracotta pots, stakes, hypertufa planters, and sieves.